Technological Advances in Surgery, Trauma and Critical Care - Latifi, Rifat; Rhee, Peter; Gruessner, Rainer W.G (Springer New York : Imprint: Springer, 2015)
This text is designed to provide a comprehensive and state-of-the-art overview of the major technological advances in the field of surgery, trauma and critical care and many aspects of surgical science and practice, is unparalleled to any other current textbook. The book has been structured to review the overall scope of most current technological advances dealing with surgery, trauma, and critical care. As such, this volume represents the most comprehensive textbook covering a wide range of topics and technological advances including genomics and nanotechnologies that affect patients' care and surgeons' practice daily. Additionally, it highlights the dramatic changes in the field of neurosurgery, ENT, cardiothoracic, vascular surgery, minimally invasive surgery, robotic assisted surgery, tissue engineering, transplant, artificial limbs, pediatric surgery and telemedicine and telepresence. Technological Advances in Surgery, Trauma and Critical Care will serve as a valuable resource for clinicians, surgeons and researchers with an interest in trauma, critical care, and all the specialties of surgery. It provides a concise yet comprehensive summary of the current status of the field that will help guide patient management and stimulate investigative efforts.